Connectivity of Semicartesian Products - Metrose Metsidik; Helin Gong (Journal of Mathematics)
Semicartesian product is defined on the basis of two special bipartite graphs and labeling of their vertices, and it has a pleasing property that it is composed of hexagonal structures. In this study, we give two formulae to calculate separately the connectivity and edge connectivity of a semicartesian product graph.